Validation and reliability of Oral Health Impact Profile-14 questionnaire among pregnant woman - Suwargiani, Anne Agustina; Pribadi, Indra Mustika Setia; Hidayat, Wahyu; Yasrin, Tadeus Arufan (Universitas Padjadjaran, 2016)
Introduction: The impact of oral health on quality of life of pregnant woman can be measured with the Oral Health Impact Profile-14 (OHIP 14). OHIP 14 is a measuring instrument that measures the functional limitations, physical pain, psychological discomfort, physical disability, psychological disorders, social disorder and disability. validity and reliability of a questionnaire is needed to measure the impact of dental health. The objectives of this study was to get the data validity and OHIP14 questionnaire reliability in pregnant woman. Methods: The research material that OHIP questionnaire 14 that has been adapted to the language and culture of Indonesia. Analysis of the questionnaire on the validity and reliability used correlation test. Research conducted by accidental sampling. Population study was pregnant woman who went to the beauty clinic in Banjaran District of Bandung. Sample study was pregnant woman. The inclusion criteria of sample is in good general state of health, exclusion criteria that do not have a systemic disorder. Result: Validity OHIP14 is the value of R calculated in the range from 0.495 to 0.647, r value calculated in 95% confidence level is 0.374 and in 99% confidence level is 0.474. The coefficient of reliability of 14 item instrument is 0.944. Conclusion: 14 OHIP questionnaire given to pregnant woman to be stated is valid and reliable.